Small Is Not Beautiful: Firm-Level Evidence of the Link between Credit, Firm Size and Competitiveness in Colombia - Arturo Galindo; Marcela Melendez (Inter-American Development Bank (IDB), 2013)
Credit has been found to be a catalyst for economic growth, as it spurs investment, enhances productivity, allows costs to be spread out over time, improves resource allocation, and enables investors to cope better with macroeconomic volatility. Most studies focus on the relationship between financial development and growth at the country level, while few analyze the relationship at the firm level. Using a panel-shaped firm-level dataset of Colombian firms and employing the methodology developed by Love and Zicchino (2006), this paper examines whether the response of firms to financial and real shocks varies according to firm size and across different levels of firm productivity. The study finds that financial shocks have a significant positive impact on firm growth, which is larger for larger firms and more productive firms that export. The results indicate that something is preventing smaller firms from taking full advantage of access to external financing.
Keywords: G32; O54; 330